The psychometric properties of the respectful maternity care (RMC) for an Iranian population - Khadije Hajizadeh; Mohammad Asghari Jafarabadi; Maryam Vaezi; Shahla Meedya; Sakineh Mohammad-Al; Mojgan Mirghafourvand (BMC, 2020)
Abstract Background The absence of Respectful Maternity Care (RMC) deters mothers from seeking maternity care services. Given the importance of RMC and the lack of a standard tool for its assessment in Iran, the present study was conducted to translate and assess the psychometric properties of the RMC questionnaire in Iranian women. Methods Forward-backward method was used for translating the questionnaire from English into Persian. A total of 265 postpartum women entered the study by simple random sampling from public and private hospitals in Tabriz, Iran. The validity of the questionnaire was confirmed through the face, content and construct validity. Construct validity was assessed through exploratory and confirmatory factor analyses. The internal consistency and test-retest reliability were used to confirm the reliability of the questionnaire. Internal consistency was examined by measuring the Cronbach's alpha in a sample of 20 mothers, and test-retest stability by calculating the Intraclass Correlation Coefficient (ICC) in the same group of mothers, who had completed the questionnaire twice with a two-week interval. Results The exploratory factor analysis led to the extraction of one factor. Item 12 was eliminated due to its low factor loading. X2/df was less than 5, and RMSEA was less than 0.08, which confirms the validity of this model. The Cronbach's alpha coefficient was obtained as 0.93 and ICC (with 95% confidence interval) as 0.98 (0.96 to 0.99). Conclusion The results of the study demonstrated that the Iranian RMC scale can be used as a valid and reliable instrument to assess RMC in Iran.